Impact of Insecurity on Secondary School Administration in North-West-Geo-Political Zone, Nigeria - Mohammed Hauwa; Ogunode Niyi Jacob (Researchparks Publishing, 2022)
Insecurity is frustrating the development of education in Nigeria. Educational institutions have been turned to field of kidnapping for bandits and insurgents. This paper analyses the impact of insecurity challenges on administration of secondary school education in North-West Nigeria. The paper employed secondary school data which were sourced from print and online medium. The paper concludes that the insecurity challenges in North- West Nigeria have led to death of teachers and students, affected achievement of education objectives, enrolment and retention of students and also led to discruption of school administration and academic calendar of the secondary schools across the zone. Based on this, the paper recommended that the federal and state government should employ every strategies to solve the problems of school attacks in the geo-political zones of Nigeria. This problem can be addressed by addressing the problem of unemployment in the region and increasing the number of security surveillance in the zone.